IMPLEMENTASI PERSAMAAN HAK NARAPIDANA TERHADAP PELAYANAN KESEHATAN PADA LEMBAGA PERMASYARAKATAN PROVINSI RIAU - Deriansyah Deriansyah; Ardiansyah Ardiansyah; Bagio Kadaryanto (Universitas Muhammadiyah Ponorogo, 2021)
In essence, correctionalization is one of the manifestations of the formal institutionalization of the public's reaction to crime. The reaction of this society at first only focused on the element of giving suffering to lawbreakers. However, in line with the development of society, the element of giving suffering must also be balanced with humane treatment by paying attention to the human rights of lawbreakers as individual beings, as well as creatures. social. Therefore, the correctional facility must also function as a place for the rehabilitation of prisoners with a variety of coaching activities. The purpose of this study is to analyze the implementation of the equal rights of prisoners to get health services at prisons in Riau province and to analyze the obstacles and efforts in implementing the equal rights of prisoners to get health services in prisons in Riau province. The research method is sociological legal research, by identifying the legal effectiveness of the law in society which discusses the Implementation of the Equality of Prisoners to Get Health Services in Prisons in Riau Province, namely in Class II A Lapas Pekanbaru and Class II B Rokan Hulu Prison. In general, the implementation of prisoners' rights in obtaining health services in prisons in Riau Province has not been able to meet the needs of prisoners in prisons. It is hoped that the government will pay special attention to the impact arising from the overcapacity of a correctional institution. Because the excess occupants (over capacity) of a correctional institution will cause a health condition that is not good for prisoners so that it will hinder the running or ineffectiveness of the implementation of development programs in prisons. It is hoped that the Government will further improve health resources, financing, infrastructure, health service efforts and maintain environmental health in prisons and fulfill the food and drinking needs of prisoners in prisons as well as special attention to the impact arising from overpopulation. capacity) of a correctional institution so that the right to health for prisoners can be fulfilled, and human rights can be protected according to the ideals of the Indonesian people as referred to in Pancasila and the 1945 Constitution of the Republic of Indonesia (UUDNRI).